Sex chromosomes and internal telomeric sequences in dormitator latifrons (Richardson 1844) (eleotridae: Eleotrinae): An insight into their origin in the genus - Paim, Fabilene Gomes [UNESP]; Nirchio, Mauro; Oliveira, Claudio [UNESP]; Rossi, Anna Rita (MDPI, 2020)
The freshwater fish species Dormitator latifrons, commonly named the Pacific fat sleeper, is an important food resource in CentralSouth America, yet almost no genetic information on it is available. A cytogenetic analysis of this species was undertaken by standard and molecular techniques (chromosomal mapping of 18S rDNA, 5S rDNA, and telomeric repeats), aiming to describe the karyotype features, verify the presence of sex chromosomes described in congeneric species, and make inferences on chromosome evolution in the genus. The karyotype (2n = 46) is mainly composed of metacentric and submetacentic chromosomes, with nucleolar organizer regions (NORs) localized on the short arms of submetacentric pair 10. The presence of XX/XY sex chromosomes was observed, with the X chromosome carrying the 5S rDNA sequences. These heterochromosomes likely appeared before 1 million years ago, since they are shared with another derived Dormitator species (Dormitator maculatus) distributed in the Western Atlantic. Telomeric repeats hybridize to the terminal portions of almost all chromosomes; additional interstitial sites are present in the centromeric region, suggesting pericentromeric inversions as the main rearrangement mechanisms that has driven karyotypic evolution in the genus. The data provided here contribute to improving the cytogenetics knowledge of D. latifrons, offering basic information that could be useful in aquaculture farming of this neotropical fish.
Keywords: (TTAGG)n; FISH; ITS; Pacific fat sleeper; RDNA; XX/XY sex system